If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+1)/3=(x-1)/5
We move all terms to the left:
(x+1)/3-((x-1)/5)=0
We calculate fractions
x/()+(-((x-1)*3)/()=0
We calculate terms in parentheses: +(-((x-1)*3)/(), so:We get rid of parentheses
-((x-1)*3)/(
We multiply all the terms by the denominator
-((x-1)*3)
We calculate terms in parentheses: -((x-1)*3), so:We get rid of parentheses
(x-1)*3
We multiply parentheses
3x-3
Back to the equation:
-(3x-3)
-3x+3
Back to the equation:
+(-3x+3)
x/()-3x+3=0
We multiply all the terms by the denominator
x-3x*()+3*()=0
We add all the numbers together, and all the variables
x-3x*()=0
| 1/2x-5=2/3x-5 | | 2x2−2x−180=0 | | 3,50x+8.50=26 | | X+4+x+50=180 | | 2+6+-6n=2 | | 10/1=4/x | | -2/3+1/2n=-1/2n | | -16x-12=40-3x | | x^2-6-360=0 | | 1/2(-4+6x)=1/3x+2/3(x+9 | | (x+5)^2=-32 | | 2x+15=3x-34 | | 6t+3(5t-4)=12(2t-5 | | 2x+x2=169 | | F(x)=4x^2-2x-7 | | 16+4x=-x+7x | | -3k-4-k=12 | | -6x+3=6x+5 | | 3/4x=6+2x | | 5c-12=-32 | | -0.7+2m=m+.9 | | 2x+9=17+6x | | r+32=77 | | -8r+8r=-3 | | 0.5x+x=x-2 | | 12-3b;=2.3 | | -18+3/8(16-40x)=8 | | 16+4K=-k+7k | | 6n+42n+42=-40+7n | | -8=-5x+3x | | 4-x-7=5 | | (6x)+13-(4x)=-7x-10+x |